2018
DOI: 10.1111/and.12979
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of CAG repeat length of the androgen receptor gene and Y chromosome microdeletions among Jordanian azoospermic infertile males

Abstract: Assisted reproductive technology is a common procedure which helps millions of couples who suffer fertility problems worldwide every year. Screening for genetic abnormalities prior to such procedure is very important to prevent the transmission of harmful genetic mutations to future generations. Microdeletions within the azoospermia factor (AZF) region of the Y chromosome and the expansion of the CAG trinucleotides in the androgen receptor (AR) gene are among the susceptible causes of male infertility in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
2
9
2
3
Order By: Relevance
“…On the other hand, the azoospermic group did not show an association with the length of the AR‐CAG repeat compared with the control group. The current results support previous reports that demonstrated a strong association between the longer AR‐CAG repeats and the oligozoospermia and teratozoospermia (Badran et al., 2009; Batiha et al., 2018; Dowsing et al., 1999; Fesai et al., 2009; Grigorova et al., 2017; Hadjkacem et al., 2004; Han et al., 2013; Khatami et al., 2015; Kukuvitis et al., 2002; Mostafa et al., 2012; Zare‐Karizi, Amin‐Beidokhti, Rahimi, & Mirfakhraie, 2016), as well as the lack of association between azoospermia and CAG repeats in the AR gene (Batiha et al., 2018). On the other hand, some studies reported a significant correlation between AR‐CAG repeat length and azoospermia in Australia, Greece, USA, Singapore, Ukraine, Iran and Baltic (Dowsing et al., 1999; Fesai et al., 2009; Grigorova et al., 2017; Kukuvitis et al., 2002; Mifsud et al., 2001; Zare‐Karizi et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the azoospermic group did not show an association with the length of the AR‐CAG repeat compared with the control group. The current results support previous reports that demonstrated a strong association between the longer AR‐CAG repeats and the oligozoospermia and teratozoospermia (Badran et al., 2009; Batiha et al., 2018; Dowsing et al., 1999; Fesai et al., 2009; Grigorova et al., 2017; Hadjkacem et al., 2004; Han et al., 2013; Khatami et al., 2015; Kukuvitis et al., 2002; Mostafa et al., 2012; Zare‐Karizi, Amin‐Beidokhti, Rahimi, & Mirfakhraie, 2016), as well as the lack of association between azoospermia and CAG repeats in the AR gene (Batiha et al., 2018). On the other hand, some studies reported a significant correlation between AR‐CAG repeat length and azoospermia in Australia, Greece, USA, Singapore, Ukraine, Iran and Baltic (Dowsing et al., 1999; Fesai et al., 2009; Grigorova et al., 2017; Kukuvitis et al., 2002; Mifsud et al., 2001; Zare‐Karizi et al., 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Several genetic studies have investigated the role of molecular determinants in the development of azoospermia, asthenozoospermia, oligozoospermia or teratozoospermia in infertile men (Al Zoubi et al., 2019; Alhalabi et al., 2013; Badran et al., 2009; BATİHA, AL‐GHAZO, ELBETİEHA, & JARADAT, 2012; Batiha et al., 2018; Hamada, Esteves, & Agarwal, 2013; Milatiner et al., 2004; Shamsi et al., 2011; Yasin et al., 2014). Due to the contradictory results, the outcomes of these studies support further molecular investigations to identify the aetiology of the above‐mentioned abnormal spermatogenesis process and infertility.…”
Section: Discussionmentioning
confidence: 99%
“…In 66 (7.5%) of 880 patients with nonobstructive azoospermia from the Middle East, but not specifying the individual nationality, AZF deletions were detected, most frequently AZFb deletions (33.3%), but also AZFbc deletions in 17% (Alhalabi et al, ). A lower incidence of AZF deletions was found in 7/142 (5%) Jordanian patients with nonobstructive azoospermia (Batiha et al, ). The highest incidence of 24% among 99 infertile men has been reported from West Azerbaijan (Omrani, Samadzadae, Bagheri, & Attar, ).…”
Section: Discussionmentioning
confidence: 99%
“…Infertility is a major health problem with associations to both genetic and environmental factors, affecting one-sixth of couples worldwide (Batiha et al, 2018[ 5 ]; Ge et al, 2014[ 19 ]). Approximately 50 % of infertility cases are attributed to male factors (Zorrilla and Yatsenko, 2013[ 67 ]).…”
Section: Introductionmentioning
confidence: 99%